A racionalidade comunicativa como método de debate para educação em direitos humanos no ensino-aprendizagem de filosofia - Oliveira, Ramando Carvalho (2020)
Using the action-research format, this dissertation under the title “Communicative rationality as a debate model for Human Rights Education on Philosophy’s teaching-learning”, objective through an practical educational intervention performed together with High School students of the public school network and analyzing the practice and challenges of a dynamic debate approach on Philosophy’s teaching-learning in connection with an proposal of Human Rights Education (HRE), organically linked to the perspective of Jürgen Habermas’ Communicative Rationality. We value the communicative skills of the students based on an understanding regarding the search for consensus using validity principles on the act of speaking, with the specificity of HRE in three thematic axes: 1) ethnic-racial diversity 2) religious and 3) sexual. In this way we look to afford the construction and problematization of a “Communicative Debate” approach, in which the students debate in significative manner in a Philosophy’s teaching-learning process themes related to social diversity. The research asserts itself by bringing to the students the perception of the necessity of coordination of their communicative skills, pointing to conversational intersections that an understanding between the parts is an essential factor for the smoothening of a consensus crisis in a sociocultural contingency marked by conflicts of discourse, communication pathologies and violations of Human Rights, both on the society as well as in the school environment